Pelatihan Pembelajaran Biologi Interaktif Untuk Guru Sekolah Pedesaan - Muhammad Zainul Muttaqin; Sri Rahmawati; Rahmad Rafid; Rosidi Azis; Aprianus Adi (Journal of Community Development, 2023)
Interactive Biology learning training for rural school teachers aims to improve the quality of teaching by utilizing learning methods that actively involve students, despite the limited resources available. This study uses a qualitative approach with phenomenological design to explore the teacher's experience and perception of the training. Data were collected through in-depth interviews, classroom observations, and documentation. The results showed that this training has a positive impact on improving the knowledge and skills of teachers in implementing interactive Biology learning. Teachers feel more confident in using simple teaching aids and environment-based experiments as a learning medium. However, the main challenge faced is the limited facilities and teaching aids in rural schools. In addition, despite the increase in student activity, teachers also face difficulties in managing the diversity of student interests and abilities. Overall, the training improves the quality of teaching in rural schools and provides practical guidance to address existing challenges. This research suggests that continuous training should be conducted and focus on practical solutions related to limited resources